Ocular contact lenses: smart materials for biomedical applications - Hajirasouliha, Elnaz; Zandi, Mojgan; Hashemi Tabatabaei, Mitra; Zarrinbakhsh, Parviz (Polymer bulletin (Berlin, Germany), 2024)
Due to population aging, lifestyle changes, coexisting medical disorders, and environmental factors, most countries have seen an increase in the prevalence of eye illnesses in recent decades. As a result of excellent knowledge on ocular disorders, patients are more likely to receive early detection and treatment, and there is a more prominent need for less invasive, more effective treatments for anterior and posterior eye disorders. Over 120 million individuals worldwide benefit from contact lens applications; however, there is room for improvement in ophthalmic therapies. Many corneal and ocular surface illnesses can be treated with therapeutic contact lenses (TCLs), which reduce pain and promote ocular healing, corneal protection, and eye drug delivery. According to studies, up to 26% of therapeutic contact lens users stop wearing contact lenses due to discomfort, such as dry eye disease. An interesting subject that is now undergoing a significant role in improving ocular lenses is materials which are highly evolving with advances in bioscience for different applications, such as drug delivery, eye wound dressing, and eye disease treatments. Silicon hydrogel and polymer acrylate-based materials are commonly used in ocular lens fabrication. With a priority on the materials science used in creating new therapeutic ocular lenses, this review offers a recently developed viewpoint on ocular lens materials to provide an outline of the upcoming outlooks and challenges in this field. Graphical abstract